2015
DOI: 10.1615/critrevimmunol.2015013607
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cell-Independent Immune-Mediated Mechanisms of Anti-Tumor Activity

Abstract: Despite the growing number of preclinical and clinical trials focused on immunotherapy for the treatment of malignant gliomas, the prognosis for this disease remains grim. Cancer immunotherapy seeks to recruit an effective immune response to eliminate tumor cells. To date, cancer vaccines have shown only limited effectiveness because of our incomplete understanding of the necessary effector cells and mechanisms that yield efficient tumor clearance. CD8+ T cell cytotoxic activity has long been proposed as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 166 publications
(171 reference statements)
1
25
0
Order By: Relevance
“…Furthermore, Saposin B also facilitated antigen cross-presentation by disintegrating membranes of apoptotic vesicles in recipient dendritic cells (DCs), resulting in activated subsequent CD8+ T cell responses [ 21 ]. It was clear that both NKT and CD8+ T cells acted as a direct killer to eliminate tumor cells and impede tumor progression [ 22 , 23 ]. Therefore, patients with lower CNPY2 isoform2 expression might have weaker immunological responses to conquer tumor progression, which could translate into a poorer survival outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Saposin B also facilitated antigen cross-presentation by disintegrating membranes of apoptotic vesicles in recipient dendritic cells (DCs), resulting in activated subsequent CD8+ T cell responses [ 21 ]. It was clear that both NKT and CD8+ T cells acted as a direct killer to eliminate tumor cells and impede tumor progression [ 22 , 23 ]. Therefore, patients with lower CNPY2 isoform2 expression might have weaker immunological responses to conquer tumor progression, which could translate into a poorer survival outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the adaptive immune system provides an effective response against tumors, mainly mediated by CD8 + cytotoxic T lymphocytes (CTLs), which induce tumor cell death through perforin-Granzyme release or via Fas/FasL pathway [13]. CD4 + T cells also play critical roles in anti-tumor responses as they indirectly stimulate CD8 + T cells by secreting pro-inflammatory cytokines that support CD8 + T cell activities [14]. In this context, infiltration of human lung tumors by CTLs has been significantly correlated with an improved outcome of NSCLC patients [1521].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has already been shown that NKT and NK cells express NOD1, and their stimulation with NOD1 agonist induces a strong IFN-γ production and enhances their cytotoxic activity. [58][59][60] However, the stimulation of innate subsets was not efficient enough in this model, which requires a strong and specific antitumor immunity to generate a solid therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%